Textile Craft Art Punch Needle Technique as an Effort to Preserve Extinct Traditional West Javanese Food as a Learning Resource in Art Education - Rahmawati Rahmawati; MC Wara Candrasari; Febi Bunga Permata Sumardi; Purwanto Purwanto (Jurnal Pendidikan Abad Ke-21, 2026)
Traditional Indonesian food items, especially those from West Java, are a fundamental part of the culture. However, according to Mei Batubara, Chair of the Pusaka Rasa Nusantara Team, traditional Indonesian food culture is currently in danger owing to the lack of regeneration concerning the cooking skills of traditional dishes. This study focused on the endangered traditional West Javanese foods and highlighted them in the form of textile artwork using punch needle technique. At the same time, it also emphasized the importance of art education in cultural preservation. The current study used a qualitative descriptive design along with literature analysis including interviews with the younger generation and observations at culinary landmarks. According to previous research conducted in 2024, there was an observation that people, especially the younger generation, like fast food more as compared to traditional Indonesian foods because the latter is not seen as practical or modern. The three disappearing traditional foods in West Java, i.e., Deblo, Ali Agrem, and Awug, inspired this research and served as inspiration in creating artworks using traditional foods. Additionally, it was concluded that art education plays a significant role in the formation of artistically trained young individuals who can preserve their culture through art. The findings demonstrate that the integration of traditional culinary heritage into fine arts curricula can foster cultural awareness, enhance creative economy potential, and ensure the continuity of local wisdom. Thus, art education not only produces aesthetic objects but also functions as a strategic instrument for cultural resilience and intercultural dialogue. The resulting textile craft pieces successfully transformed extinct culinary forms into durable visual narratives, suggesting that art education-based preservation strategies offer sustainable alternatives to oral transmission alone.